P175 Prognostic value of 99mTc-ECD brain perfusion SPECT in patients with atrial fibrillation and dementia. (13th January 2020) - Hashimoto, H; Nakanishi, R; Mizumura, S; Hashimoto, Y; Okamura, Y; Yamanaka, K; Ikeda, T
Abstract: Background: Atrial fibrillation (AF) is the most common cardiac arrhythmia, and those afflicted have reduced quality of life, functional status, and cardiac performance. The patients with AF have a high risk of coronary heart disease and cardiovascular disease. Although the prevalence of AF is increasing, cognitive disorders are also on the rise in tandem with the aging of the population. The patients with dementia have also experienced lower the quality of life and have increased mortality. Technetium 99m ECD brain perfusion single photon emission computed tomography (99mTc-ECD brain perfusion SPECT) is a useful modality for diagnosing dementia and identifying high risk patients with mild cognitive impairment. However, there are few reports about the relationship between the value of Z score calculated by 99mTc-ECD brain perfusion SPECT and prognosis of patients with AF and dementia. Purpose: The aim of this study was to evaluate the prognostic values of brain perfusion using 99mTc-ECD SPECT in patients with AF and dementia. Methods: Among 405 consecutive patients who were diagnosed as AF in cardiac outpatients and subsequently diagnosed as dementia using Mini-Mental State Examination by neurologists or psychiatrists, we identified 170 patients (81 ± 10 years) who underwent 99mTc-ECD brain perfusion SPECT for the current study. Of those, 73, 73, and 24 were diagnosed as Alzheimer's dementia (AD), vascular dementia (VD), and non-specified dementia respectively. Multivariate Cox model was used to assess if higher Z score by 99mTc-ECD brain perfusion SPECT and clinical parameters were associated with major adverse cardiovascular events (MACE) including cardiac death, myocardial infarction, hospitalization for heart failure, and stroke. Sub-analyses of multivariate Cox models by AD or VD were also assessed. The cut-off values of Z score were determined using area under the curve by a receiver operating characteristic analysis based on MACE occurrences. Results: During a mean follow-up of 1258 ± 1044 days, 62 MACE occurred. There was not significant difference of MACE between AD and VD (33%, vs. 44%, p = 0.153). By multivariable Cox model, the higher Z score of temporal-occipital-pariental lobe was associated with increased MACE compared to the lower group (HR 2.521, 95% CI 1.465–4.337, p < 0.001). In a sub-analysis of patients with AD, Z score was the most significant prognostic factor for MACE (HR 3.969, 95% CI 1.374–11.468, p = 0.011). The similar trend was observed in those with VD (HR 2.247, 95% CI 1.028–4.913, p = 0.043). Conclusion: This study demonstrated that the Z score of temporal-occipital-pariental lobe by 99mTc-ECD brain perfusion SPECT could be a potential prognostic value among patients with AF and dementia, regardless of type of dementia.